Hepatitis C - cure of infection - Mailliard, Mark (Henry Stewart Talks, 2016)
HCV: major milestones, Hepatitis C virus & infection, Hepatocellular cancer, HCV natural history and therapy, HCV RNA and protein, HCV genotypes and subtypes, Hepatitis C vaccine, Direct acting antivirals (DAAs)